2001
DOI: 10.1309/vp4w-5c55-7m09-6tx3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HER2/neuStatus Assessed by Quantitative Polymerase Chain Reaction and Immunohistochemistry

Abstract: We prospectively evaluated a series of 254 breast cancers by quantitative polymerase chain reaction (PCR) and immunohistochemistry using 3 antibodies: HercepTest, CB11, and TAB250. DNA was extracted from a 10-micron tumor section for PCR, and 4-micron serial sections were taken from the same block for immunohistochemistry. The immunohistochemical results were scored using a semiquantitative immunohistochemical system. A positive tumor by immunohistochemistry had a score of 5 or more. The manufacturer's recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 28 publications
5
35
0
1
Order By: Relevance
“…With this staining kit, the rate of HER2-overexpressing bladder carcinomas was 41% in our study, which represents a roughly equivalent rate to that reported for breast carcinomas. 46,47 There is evidence of a correlation between worse prognosis and immunohistochemic HER2 overexpression in bladder cancer. Lipponen 31 reported that HER2 expression predicted recurrence-free survival in superficial tumors with a borderline significance.…”
Section: Resultsmentioning
confidence: 99%
“…With this staining kit, the rate of HER2-overexpressing bladder carcinomas was 41% in our study, which represents a roughly equivalent rate to that reported for breast carcinomas. 46,47 There is evidence of a correlation between worse prognosis and immunohistochemic HER2 overexpression in bladder cancer. Lipponen 31 reported that HER2 expression predicted recurrence-free survival in superficial tumors with a borderline significance.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained in our own institution. 51 The amplification of this gene has been found in 0% of special type cancers and o1% of invasive lobular carcinomas. 52 In the latter study, only one of 67 invasive lobular carcinomas was positive for HER2/neu gene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…As two cores from each tumor were assessed, the larger of the two values was chosen for use in statistical analysis to minimize the effect of false negatives on the array. For ER, PgR, HER2, and p53, cutpoints to define positivity were based on previous validation studies (34,(36)(37)(38)(39). For CK5 and EGFR, the cutpoint for positivity was arbitrarily specified as !4.…”
Section: Patient Cohort and Clinical Follow-upmentioning
confidence: 99%